(untitled) (CIPEEX, 2025)
Introduction: Cerebral palsy refers to a permanent condition in which there is dysfunction of tone, movement, or posture. It is a disease that does not progress, but due to neuroplasticity, the prognosis can change according to the child’s development 1,2. Children may have compromised motor areas, developing spasticity and muscle weakness. This impairment causes increased excursion of the point of gravity, mainly due to spasticity, muscles shortened to the size of the bones, and hip dysplasia, which mainly promote muscle weakness3 .Patients with cerebral palsy can be classified according to spasticity criteria as hemiplegic, diplegic, or quadriplegic 4,5 .During a physiatry residency at the CRER rehabilitation hospital, it was observed that there was a risk of loss of strength after botulinum toxin injections in patients with spasticity in cerebral palsy, as there is a still unclear gap between the higher prevalence of spasticity and/or weakness in patients with cerebral palsy. Objective: To investigate the interaction between muscle strength and spasticity in hemiplegic and diplegic children with cerebral palsy classified as I-III according to the GMFCS motor scale. Factors such as botulinum toxin, tendon tenotomy surgeries, and patients undergoing physical therapy will be considered. Methods: An observational, cross-sectional, analytical field study will be conducted. The sample will include 30 ambulatory participants with hemiplegic and diplegic cerebral palsy, regardless of gender, aged 8 to 18 years, and with a good level of comprehension. The study will be conducted at the CRER hospital, where patients will be selected through medical records through a convenience sample. Participants will then be assessed for strength using a SP-TECH dynamometer, spasticity, the Ashworth scale, and botulinum toxin administration, surgeries, and physical therapy follow-up. Results: The research has already been approved by the CRER ethics committee, data have already been collected from one patient, in which, upon physical examination, Ashworth 2 was observed in the right triceps surae and Ashworth 1+ in the left, reducible to neutral; Gait with equinus foot on the right. IN THE EXAMINATION OF STRENGTH and ASYMMETRY BY THE SP-TEACH APPARATUS: KNEE FLEXION ASYMMETRY 34% KGF STRENGTH: Left: 8.97 Right: 13.69 KNEE EXTENSION ASYMMETRY 12% KGF STRENGTH: Left: 9.19 Right: 10.48 HIP ABDUCTION ASYMMETRY 25% KGF STRENGTH: Left: 9.39 Right: 7.05 HIP ADUCTION ASYMMETRY 16% KGF STRENGTH: Left: 9.52 Right: 8.02 ANKLE DORSAL FLEXION ASYMMETRY 37% KGF STRENGTH: Left: 6.27 Right: 9.88 ANKLE PLANTAR FLEXION ASYMMETRY 45% STRENGTH KGF: Left: 6.04 Right: 10.96. Conclusion: Patient with greater asymmetry (45%) in relation to the Triceps Surae muscles, since the right one has greater strength (KGF 10.96) and greater spasticity Ashworth 2+, in relation to the left one. Botulinum toxin was applied in equal amounts in bilateral gastrocnemius and soleus. Tests suggest that the Triceps Surae on the left is weaker, so the amount of toxin should be individualized, to improve the patient’s gait and functionality.